BRICS Countries’ De-Dollarization Strategy and Implementation - Li, Xue; Wen, Li-li; Aidarbayev , S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Since the mid-20th century, the US dollar has been the most popular currency in the global financial system and plays the most important role in global transactions. However, today, the BRICS countries have all started the process of de-dollarization. This article takes Russia, one of the BRICS countries, as an example to briefly describe its de-dollarization process. Furthermore, although the de-dollarization strategy of the BRICS countries will bring certain inconveniences in terms of economy and system, it will still bring many advantages to make up for it. Due to the two internal driving forces of economic scale and resource scale, the BRICS countries have to and will inevitably implement this strategy. This article then analyzes the specific measures of the “BRICS countries” to de-dollarize at the economic level and institutional structure level. Eventually, the perspective focuses on China and puts forward a series of meaningful strategic implementation suggestions for China to further deepen the de-dollarization strategy. These measures can increase the proportion of the RMB in the regional economy and the world economic cycle, further facilitating the de-dollarization strategy of the BRICS countries.